The Beneficial of Social Media Platform Strategy on Firm Financial Performance - Auliya Zulfatillah; Rian Abrory (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study is to empirically prove the effect of social media use on the company's financial performance. This research is quantitative research, the data is processed with multiple linear regression models to analyse the effect of social media use on the company's financial performance. The proxies used to measure social media used are brand awareness, brand engagement, and word of mouth. The results concluded that the use of social media through the proxy of word of mouth affects the company's financial performance in the short term. This study uses social culture theory to explain the benefits of social capital that will be obtained by companies when deciding to join social media, where companies that use social media will receive more information so that they have greater social capital to support their company's financial performance.